2022
DOI: 10.1080/03019233.2022.2036307
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of coke from biomass char modified by vapour deposition of tar generated during pyrolysis of woody biomass

Abstract: In this study, in order to use woody biomass for coke production, carbon/carbon composites are first prepared using the vapour deposition (VD) method, whereby gaseous-tars generated by the pyrolysis of pine sawdust is deposited onto the pyrolysed pine sawdust char by a vertical flow-type fixed-bed reactor with pyrolysis and VD zones. Then, coke properties and gasification reactivity of composite and composite/coal blends are investigated to clarify the binder effect of biomass tar on the properties of prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The calorific value of biochar is between 7200~7560 Kcal/kg, which is higher than the standard value (7000 Kcal/kg), indicating that biochar can be a suitable substitute for traditional fossil fuels and has the potential to reduce carbon dioxide emissions in the ironmaking industry. Yuuki, M et al [32] used woody biomass to produce coke and used vapor deposition (VD) and other methods to explore the properties of coke and the study of composite/coal mixtures for gasification reactions; they determined that the optimal coal blending amount depends on the type of caking coal. It was found that 3-15 wt% of biomass can be used as coke addition for coke production.…”
Section: Application Of Biochar In Coking Processmentioning
confidence: 99%
“…The calorific value of biochar is between 7200~7560 Kcal/kg, which is higher than the standard value (7000 Kcal/kg), indicating that biochar can be a suitable substitute for traditional fossil fuels and has the potential to reduce carbon dioxide emissions in the ironmaking industry. Yuuki, M et al [32] used woody biomass to produce coke and used vapor deposition (VD) and other methods to explore the properties of coke and the study of composite/coal mixtures for gasification reactions; they determined that the optimal coal blending amount depends on the type of caking coal. It was found that 3-15 wt% of biomass can be used as coke addition for coke production.…”
Section: Application Of Biochar In Coking Processmentioning
confidence: 99%